Comparison of Effect of Treatment with Etidronate and Alendronate on Lumbar Bone Mineral Density in Elderly Women with Osteoporosis - Iwamoto, Jun (Yonsei University College of Medicine, 2005)
The purpose of this open-labeled prospective study was to compare the treatment effects of cyclical etidronate and alendronate on the lumbar bone mineral density (BMD), bone resorption, and back pain in elderly women with osteoporosis. Fifty postmenopausal women with osteoporosis, age ranging from 55 to 86 years (mean: 70.7 years), were randomly divided into two groups with 25 patients in each group: the cyclical etidronate group (etidronate 200 mg daily for 2 weeks every 3 months) and the alendronate group (5 mg daily). The BMD of the lumbar spine (L1-L4) measured by DXA, the urinary cross-linked N-terminal telopeptides of type I collagen (NTX) level measured by the enzyme-linked immunosorbent assay, and back pain evaluated by the face scale score were assessed at baseline, 6 months, and 12 months. There were no significant differences in baseline characteristics including age, body mass index, years since menopause, lumbar BMD, urinary NTX level, and face scale score between the two treatment groups. Etidronate treatment sustained the lumbar BMD following a reduction in the urinary NTX level and improved back pain, while alendronate treatment reduced the urinary NTX level more significantly, resulting in an increase in the lumbar BMD, and similarly improved back pain. No serious adverse events were observed in either group. This study confirmed that alendronate treatment had a greater efficacy than etidronate treatment in increasing the lumbar BMD through the reduction of bone resorption in elderly women with osteoporosis.